2011
DOI: 10.1017/s0033291711001772
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of mortality associated with social isolation in older men: only when feeling lonely? Results from the Amsterdam Study of the Elderly (AMSTEL)

Abstract: Background. Loneliness has a significant influence on both physical and mental health. Few studies have investigated the possible associations of loneliness with mortality risk, impact on men and women and whether this impact concerns the situation of being alone (social isolation), experiencing loneliness (feeling lonely) or both. The current study investigated whether social isolation and feelings of loneliness in older men and women were associated with increased mortality risk, controlling for depression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
163
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(182 citation statements)
references
References 52 publications
13
163
2
1
Order By: Relevance
“…Similar results were obtained by Avalud who concluded that the risk of becoming disabled of a person suffering from 4 chonic diseases is increased 4-fold [46]. Chronic diseases are the leading cause of disability, and the dependence of the elderly, together with low incomes, are the main reason for the use of social welfare benefits [47].…”
Section: Discussionsupporting
confidence: 75%
“…Similar results were obtained by Avalud who concluded that the risk of becoming disabled of a person suffering from 4 chonic diseases is increased 4-fold [46]. Chronic diseases are the leading cause of disability, and the dependence of the elderly, together with low incomes, are the main reason for the use of social welfare benefits [47].…”
Section: Discussionsupporting
confidence: 75%
“…In addition, depression (P = .04, HR = 1.81) and social isolation (P = .04, HR = 2.25) predicted mortality independent of demographics, clinical status, and treatment. 44 • When a prospective cohort study 45 of 4000 adults aged 65 to 84 years were followed for 10 years in the Netherlands, significantly more lonely men than women died. After controlling for other potentially explanatory variables (social isolation, psychiatric disorders, medical conditions, cognitive functioning, functional status, and sociodemographic factors), the mortality HR for loneliness was 1.30 (95% CI, 1.04-1.63) in men and 1.04 (95% CI, 0.90-1.24) in women.…”
Section: Detrimental Effects Of Social Isolation On Healthmentioning
confidence: 99%
“…The study authors concluded that loneliness but not social isolation was a major risk factor for higher mortality in older men. 45 • In contrast to the Dutch study, 45 a 2013 United Kingdom assessment of 6500 men and women 52 years and older over 7.25 years found that although loneliness and social isolation were both associated with increased mortality, after adjusting for other potentially influential variables, social isolation remained significantly associated with mortality (HR = 1.26; 95% CI, 1.08-1.48 for the most isolated), whereas loneliness did not (HR = 0.92; 95% CI, 0.78-1.09), indicating that social isolation was an independent factor raising mortality, but loneliness was not. 10 • To more closely examine the relationship between social isolation and mortality and to compare the predictive power of social isolation to that of traditional risk factors (elevated cholesterol, hypertension, smoking, obesity), California investigators used a nationally representative sample of 16 849 adults and found that socially isolated men and women had higher mortality than less socially isolated individuals and that social isolation predicted mortality for both genders, as did smoking and high blood pressure.…”
Section: Detrimental Effects Of Social Isolation On Healthmentioning
confidence: 99%
“…Loneliness is a negative experience (Dahlberg 2007;De Jong Gierveld 1998;Peplau and Perlman 1982) observed to be related to negative effects on well-being (De Jong Gierveld 1998) and physical and mental health (Hawkley and Cacioppo 2010;Heinrich and Gullone 2006;Holwerda et al 2012;Ó Luanaigh and Lawlor 2008;Routasalo and Pitkala 2003;Shankar et al 2013). We assume that due to its negative impact on people's lives, lonely people generally do not want to remain that way and try to overcome their loneliness.…”
Section: Introductionmentioning
confidence: 99%